2010
DOI: 10.1002/jssc.201000553
|View full text |Cite
|
Sign up to set email alerts
|

Potential of a metal–organic framework as a new material for solid‐phase extraction of pesticides from lettuce (Lactuca sativa), with analysis by gas chromatography‐mass spectrometry

Abstract: The metal-organic framework (∞)[(La(0.9)Eu(0.1))(2)(DPA)(3)(H(2)O)(3)] was tested for extraction of pyrimicarb, procymidone, malathion, methyl parathion and α- and β-endosulfan from lettuce, with analysis using GC/MS in SIM mode. Experiments were carried out in triplicate at two fortification levels (0.1 and 0.5 mg/kg), and resulted in recoveries in the range of 78-107%, with RSD values between 1.6 and 8.0% for (∞)[(La(0.9)Eu(0.1))(2)(DPA)(3)(H(2)O)(3)] sorbent. Detection and quantification limits ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 22 publications
(25 reference statements)
0
21
0
1
Order By: Relevance
“…We compared the recovery percentages obtained for pirimicarb and procymidone at a fortification level of 500.0 μg/kg with published values by Barreto . We noted that the analyte interaction with the matrix influenced the process of sorption, even when we used MOF as sorbent.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We compared the recovery percentages obtained for pirimicarb and procymidone at a fortification level of 500.0 μg/kg with published values by Barreto . We noted that the analyte interaction with the matrix influenced the process of sorption, even when we used MOF as sorbent.…”
Section: Resultsmentioning
confidence: 92%
“… used MOF containing lanthanide ions for the extraction of pesticides in five samples of graviola, soursop exotic fruit ( Annona muricata ), applying the MSPD technique. In work carried out by our group, we observed that MOF based on lanthanum and dipicolinate linkers are efficient for pesticide extraction MSPD at low cost. However, these results were obtained from the application of MOF in an analytical method developed and previously validated using silica gel and neutral alumina as the sorbents.…”
Section: Introductionmentioning
confidence: 98%
“…Although on-line SPE has the advantages of automation, MOFs with suitable particle size and good mechanical stability for on-line SPE are currently quite limited. In any case, a number of MOFs have been explored as novel sorbents for diverse SPE applications, mainly under the SPE variant matrix solid-phase dispersion (MSPD) [10][11][12][13], not necessarily in on-line approaches, and combined with high-performance liquid chromatography (HPLC) [9,14,15] or gas chromatography (GC) [10][11][12][13], as separation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have been successfully explored as sorbents for solid-phase extraction (SPE) [18][19][20][21][22][23][24], solid-phase microextraction [25][26][27], and as stationary phases of chromatography column [28][29][30][31][32][33]. Recently, MOFs-based SPME researches have received an increasing interest in analytical science.…”
Section: Introductionmentioning
confidence: 99%